In vitro immunomodulatory effect of Pouteria cambodiana (Pierre ex Dubard) Baehni extract - A. Manosroi (2018)
The methanolic stem bark extract from Pouteria cambodiana (Pierre ex Dubard) Baehni was evaluated for immunomodulating activity on BALB/c mice. The antioxidant effect was also assessed. The extract presented a good dose-response effect in the peritoneal macrophage phagocytosis assay with higher activity at 1 mg/ml and an EC50of 0.02 mg/ml and also activated lysosomal enzyme activity with an EC50of 0.16 mg/ml. In the splenocyte proliferation assay, the extract without mitogen was active (EC50, 0.01 mg/ml) while the EC50of the extract with lipopolysaccharide (LPS) and pokeweed mitogen (PWM) were 0.02 and 0.41 mg/ml, respectively. The extract showed low free radical scavenging activity in the 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical assay with an IC50of 0.24 mg/ml, being less active than ascorbic acid, butylated hydroxytoluene (BHT) and α-tocopherol which showed IC50of 0.08, 0.10 and 0.11 mg/ml, respectively. The extract at doses up to 0.073 mg/ml had no effect on lipid peroxidation. The potent immunological but no antioxidant activity of the extract presented in this study can explain, at least in part, the Thai folklore application of this plant in the treatment of fever and skin eruption. © 2005 Elsevier Ireland Ltd. All rights reserved.